FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN MEMBAYAR PAJAK PADA WAJIB PAJAK ORANG PRIBADI YANG MELAKUKAN PEKERJAAN BEBAS - Afifah Ezra Ermida, 11.05.52.0094; Nuswandari, Cahyani (Students Journal of Accounting and Banking, 2015)
This research to showed factors that affect enforcement for paying taxes. As these factors is realization ofÂ tax paying, awareness of tax paying, knowlodge and understanding of tax regulations, a good perception of the effectiveness taxation system, and the confidence level of the government system and law. The sampling method used random sampling. Relationship and influence between variable is described by using multiple regression analysis. The hypothesis test showed that the awareness of tax paying, knowlodge and understanding of tax regulations, a good perception of the effectiveness of taxation system significant positive effect of enforcement for paying taxes. While the confidance level of the government system and law are not significant to enforcement for paying taxes.Keywords: Enforcement for Paying Taxes, Awareness of Tax Paying, Knowlodge and Understanding of Tax Regulations, A Good Perception of The Effectiveness of Taxation System, The Confidence Level of The Government System and Law Â